Islamic Education Institutions Based On Local Wisdom: (Study Of Mustafawiyah Madina Islamic Boarding School) - Sapirin Sapirin (CV. Pusdikra Mitra Jaya, 2022)
This article examines the concept and implementation of Islamic educational institutions based on local wisdom. This research was conducted at the Islamic Boarding School Musftafawiyah Madina. The research method used to obtain data uses qualitative methods with a naturalistic or descriptive approach. Data analizy used organized data and than reduksi and conclusion. The results of the study found that first, the Purbabaru Mustafawiyah Islamic Boarding School was to produce scholars who had good morals based on the ahlus sunnah wal jama'ah who belonged to the Shafi'i school. second, the existence of Islamic boarding schools has a very important task to overcome the problems of modern society. So, in addition to being a place to gain religious knowledge, it is also useful as a means of character building and morality so that they are able to play a role in society. So in this case, the Musthafawiyah Islamic Boarding School cadres the students to be able to master religious knowledge as well as general knowledge. Knowledge gained through recitation activities and schools sheltered by Islamic boarding schools. Meanwhile, character is formed through all actions and activities of students carried out in Islamic boarding schools which always get monitoring from kyai, caregivers, and boarding school administrators. Third, in the social context of the Mandailing Natal community, which is rich in local wisdom, which can be a motivation and foundation for life to re-knit the image of a nation that is respected, dignified, and has the shawl of civilization in the eyes of the world. Of course, this cannot be separated from how to strengthen the education system, both formal and non-formal, as the main basis in directing the movement of the younger generation in the future, including the students at the Musthafawiyah Islamic Boarding School.